The Constitution of Somaliland: The Problem of Constitutional Generations and Clan Dissolution - Aguilar, Mario I. (Scientific Research, 2015)
This paper outlines the history, formation and general principles of the 2001 Somaliland Constitution. The people of Somaliland declared independence from Somalia in 1991 returning to the boundaries that had marked the British Protectorate of Somaliland until 1960, holding successful democratic elections, and establishing peace and stability, becoming an exception state within a war-torn region. In a contribution to the sociology of law and the wider knowledge of Somaliland this paper outlines the unifying principles within the Constitution, principles that are taken from the unity of religion (Islam), and the desire to exercise unity in diversity through traditional institutions of conflict resolution with the inclusion of universal principles of human rights law.
Keywords: Somaliland; African Constitutions; Sociology of Law; Sociology of Religion; Karl Mannheim; Constitutional Generations; Islam in the Horn of Africa; State Formation